2007
DOI: 10.1007/s00436-007-0639-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of a chemotherapy effect on the cuticular surface of Wuchereria bancrofti adult worms in vivo

Abstract: Wuchereria bancrofti is the main species responsible for human lymphatic filariasis and remains a major public health problem in tropical countries around the world. Diethylcarbamazine (DEC) has been used for decades in control programs as an effective microfilaricide, although its efficacy in killing adult worms is only around 50% and its direct mode of action is unclear. Recently, in an attempt to control and eliminate lymphatic filariasis, WHO has recommended albendazole (ALB), a broad-spectrum anthelminthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The striations on the cuticle are actually the annulations of the cuticle. The results obtained showed that the structure of parasite wall is similar to the surface of W. bancrofti (Araujo, 1995;Oliveira-Menezes, 2007). The results support the use of S. digitata as a model organism for research in filariasis.…”
Section: Discussionsupporting
confidence: 67%
“…The striations on the cuticle are actually the annulations of the cuticle. The results obtained showed that the structure of parasite wall is similar to the surface of W. bancrofti (Araujo, 1995;Oliveira-Menezes, 2007). The results support the use of S. digitata as a model organism for research in filariasis.…”
Section: Discussionsupporting
confidence: 67%
“…Surface distortion and loss of regular cuticular annulations were also observed on Brugia malayi Brug (Tippawangkosol et al, 2004). Adult Wuchereria bancrofti Wucherer & Bancroft subjected to albendazole and diethylcarbamazine combination therapy exhibited swollen cuticle, formation of spherical and spike-like projections at the anterior region, and leaf-like expansion on the general cuticle (Oliveira-Menezes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological alterations as antihelminthic outcome was also observed by Oliveira-Menezes et al (2007) who demonstrated cuticular changes of the W. bancrofti adult worm surface obtained from a patient treated with diethylcarbamazine (DEC) co-administered with albendazole (ALB). On the other hand, adult worms that were recovered from a patient treated with DEC alone after a single dose did not show such any abnormalities.…”
Section: Discussionmentioning
confidence: 82%
“…It is not possible, however, to understand whether or not these alterations have biological significance on the parasite itself or in the host-parasite interplay at longer time if would have an accumulative damage after yearly mass treatment as discussed by Ottesen et al (1997) and Oliveira-Menezes et al (2007) commenting on comparative analysis of a chemotherapy effect on the cuticular surface of Wuchereria bancrofti adult worms.…”
Section: Discussionmentioning
confidence: 99%